KOMPETENSI PEDAGOGIK GURU TERHADAP PEMBENTUKAN SIKAP ANAK USIA DINI - Nurul Fajriah; Ayi Teiri Nurtiani (Jurnal Buah Hati, 2022)
Preferably, pedagogical competence in PAUD teachers is prioritized because the teacher's role is not only as an educator, but this competency has a very large role in the learning process because PAUD teachers must be able to plan educational program activities, carry out the process of education, care, and protection. as well as carrying out assessments based on developmental aspects according to the characteristics of early childhood and their impact on the formation of early childhood attitudes. The purpose of this study is to describe the development and application of teacher pedagogic competence and its impact on the formation of early childhood attitudes. This research method is descriptive qualitative through interviews, questionnaires and observation sheets which are then analyzed using the triangulation method. Based on the results of the data obtained, it can be concluded that the pedagogical competence of PAUD teachers in Khairani Kindergarten is very good (97%). It can be seen from the teaching given which is always innovative with actual learning developments so that it appears that PAUD teachers are open to anything new as long as it stimulates various aspects of development. optimum child. Great support was also provided by the school which facilitated this development with various infrastructure, training activities and competitions. Of course, this also has a big impact on the development of good attitudes (66.2%) displayed by early childhood during learning activities in the classroom because it creates an atmosphere and atmosphere for learning that is optimistic, positive, conducive, effective and efficient.AbstrakSeyogyanya kompetensi pedagogik pada guru PAUD merupakan hal yang diutamakan dikarenakan peran guru bukan hanya sebagai pendidik semata, bahkan kompetensi tersebut sangat memiliki peran yang besar dalam proses pembelajaran karena guru PAUD harus mampu membuat perencanaan kegiatan program pendidikan, melaksanakan proses pendidikan, pengasuhan, dan perlindungan, serta melaksanakan penilaian berdasarkan aspek perkembangan sesuai dengan karakteristik anak usia dini serta dampaknya terhadap sikap anak usia dini. Berdasarkan hasil data yang diperoleh dapat disimpulkan bahwa kompetensi pedagogik guru PAUD di TK Khairani sangat bagus (97%) terlihat dari pengajaran yang diberikan selalu terperbaharui dengan perkembangan pembelajaran terbaru sehingga terlihat bahwa guru-guru PAUD terbuka dengan segala sesuatu yang baru selama menstimulasi berbagai aspek perkembangan anak dengan optimal. Tentu saja, hal ini juga berdampak besar pada pengembangan sikap yang baik (66,2%) yang ditampilkan oleh anak usia dini pada saat kegiatan pembelajaran di ruang kelas karena tercipta atmosfir dan suasana pembelajaran yang optimis, positif, kondusif, efektif dan efisien berbasis pada kemampuan abad 21 yakni 4C (critical thinking, creative thininking, collaboration, and communicatioan).